Teniases caused by Taenia asiatica, Taenia saginata, Taenia solium - S. B. Chuelov; A. L. Rossina (LLC "Diagnostics and Vaccines", 2021)
The urgency of the problem of human teniases is due to the widespread prevalence of these parasitoses, which often infect humans.The aim and result of the work is to summarize the available information about the etiology, epidemiology, pathogenesis, clinical picture, diagnosis, etiotropic therapy and prevention of human teniases.Conclusion. Teniases are widespread, including on the territory of Russia. The clinic mainly includes symptoms of lesions of the gastrointestinal tract, allergic reactions. Diagnostics is carried out on the basis of the detection of eggs, proglottids, coproangigens of parasites in the feces, serological and molecular genetic tests. Praziquantel is an effective etiotropic therapy. Prevention takes into account the peculiarities of the epidemiology of teniases.